Assessing dietary intake in accordance with guidelines: Useful correlations with an ingesta-Verbal/Visual Analogue Scale in medical oncology patients. Issue 4 (August 2019) - Guerdoux-Ninot, Estelle; Flori, Nicolas; Janiszewski, Chloé; Vaillé, Arnaud; de Forges, Hélène; Raynard, Bruno; Baracos, Vickie E.; Thezenas, Simon; Senesse, Pierre
Summary: Background & aims: Energy intake and food ingesta are central in nutritional screening and assessment. Cancer patients are at nutritional risk of losing weight, and clinicians need quick and easy tools to identify patients for nutritional support. This study aimed to evaluate the feasibility and the accuracy of a Visual/Verbal Analogue Scale of food ingesta ( ingesta -VVAS) to assess energy food intake and nutritional risk in medical oncology patients. Methods: Dieticians administered prospectively the ingesta -VVAS in 1762 medical oncology patients . The external validity of the ingesta- VVAS was determined against daily energy intake based on a 24-h dietary recall. Patients had to estimate how they currently ate on a scale from 0 " nothing at all " to 10 " as usual ". Area Under the Receiver-Operating Characteristics (ROC) curve served as determine the optimal cut-off and provide the discriminative power of the tool to detect patients who ingested less or more than 25 kcal kg −1  day −1 . Results: The feasibility of the ingesta -VVAS was 97.7%. The scores were significantly correlated with energy intake ( ρ  = .67, p < .05), whatever the specific situation ( i.e. malnutrition or not). With a cut-off of ≤7, the ingesta -VVAS exhibited a good power discrimination (AUC = .804) to detect patients who ingested less or more than 25 kcal kg −1  day −1, with a sensitivity of 80.8%, a positive predictive value of 83.6%, a specificity of 67.5%, and a negative predictive value of 63.3%. Patients with a score ≤7 on the ingesta -VVAS score were at 12-fold higher probability of nutritional risk [OR 12.3; 95% CI (8.7–17.4); p < .001]. Sensitivity to detect patients with a significant weight loss was 71%, and a positive predictive value of 75.9%. Conclusions: This easy-to-use ingesta- VVAS is well-correlated with energy intake and may be useful in clinical practice. An ingesta- VVAS score is ≤ 7 could be used to detect patients with nutritional risk of weight loss in medical oncology.